EFEK PEMODERASIAN STATUS KEPEGAWAIAN PADA PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN - I Gusti Ngurah Widnyana; Desak Ketut Sintaasih; I Gede Riana (Faculty of Economics and Business Udayana University, 2016)
The study aims to analyze difference in motivation, organizational commitment, and performance amongpermanent and outsourced employees, as well as the moderating effect of employment status on the influenceof motivation and organizational commitment to employee performance. This research was conducted in PT.Bank Rakyat Indonesia (Persero) Tbk. Kanwil Denpasar, with samples of 67 permanent employees and 67outsourced employees. Analysis technique using Anova and Moderated Regression. The results show thatthere is no significant difference between motivation and performance of permanent and outsourced employees,while there are significant difference between two kinds of employee in organizational commitment.Additionally, employee status emerges as moderating variable of influence of motivation and organizationalcommitment on employee performance. The research can become a reference for the company in improvingemployee performance in relation with employment status, motivation, and organizational commitment.